Pengembangan E-Modul Fikih Berbasis Integratif Menggunakan Flip PDF Corporation untuk Siswa MTs - Ria Nofia; Fadriati Fadriati; Nurlaila Nurlaila; Annisaul Khairat (ISLAMIKA, 2023)
The lesson material in Class VIII Fiqh subject at MTsN 5 Tanah Datar does not vary and is less attractive to students so based on a needs analysis an integrative-based e-module is needed using Flip Pdf Corporation. This study aims to determine the results of the validity and results of the practice of integrative-based e-modules on the subject matter of halal and haram food and beverages in Islamic Jurisprudence subjects at MTsN 5 Tanah Datar. The research method used is research and development (research and development) of the 4D model through four stages of define, design, develop and disseminate. The research that the researchers did was only the 3 D stage, namely define, design, develop. The test subjects in this study were 26 class VIII students. The instruments for collecting data in this study were validity sheets and practicality sheets. Quantitative data analysis techniques in this study used Aiken V with a minimum validity and practicality score of 71. Qualitative data analysis techniques used quantitative descriptive data analysis techniques. The results of this study indicate that the results of validating the development of an integrative Jurisprudence module on halal and haram food materials using the Flip Pdf Corporation application for Madrasah Tsanawiyah is 83% with a very valid category. While the practicality result is 88% in the very practical and usable category.